Correction to: Scientific Reports https://doi.org/10.1038/s41598-020-70580-3, published online 13 August 2020

The original version of this Article contained an error in Equation 1.

$${W}_{GF}\left(\varphi \right)=\frac{1}{\sqrt{2\pi {\sigma }^{2}}}\mathrm{exp}\left(-\frac{1}{2}\cdot {\left(\frac{3}{N}\sqrt{\frac{{\left(2n-1\right)}^{2}{\varphi }^{2}}{2}}\right)}^{2}\right)$$
(1)

$${W}_{GF}\left(\varphi \right)=\frac{1}{\sqrt{2\pi {\sigma }^{2}}}\mathrm{exp}\left(-\frac{1}{2}\cdot {\left(3\cdot \frac{2n-1}{2N}\right)}^{2}\right)$$
(1)

As a result, Equation 2 was incorrect.

$$R\left(\lambda \right)=\sum_{n=1}^{N}R\left(\lambda ,{\varphi }_{n}\right)\cdot {W}_{NA}\cdot {W}_{GF}=\sum_{n=1}^{N}R\left(\lambda ,{\varphi }_{n}\right)\frac{2n-1}{{N}^{2}} \frac{1}{\sqrt{2\pi {\sigma }^{2}}}\mathrm{exp}\left(-\frac{1}{2}{\left(\frac{3}{N}\sqrt{\frac{{\left(2n-1\right)}^{2}{\varphi }_{n}^{2}}{2}}\right)}^{2}\right)$$
(2)

$$R\left(\lambda \right)=\sum_{n=1}^{N}R\left(\lambda ,{\varphi }_{n}\right)\cdot {W}_{NA}\cdot {W}_{GF}=\sum_{n=1}^{N}R\left(\lambda ,{\varphi }_{n}\right)\frac{2n-1}{{N}^{2}} \frac{1}{\sqrt{2\pi {\sigma }^{2}}}\mathrm{exp}\left(-\frac{1}{2}\cdot {\left(3\cdot \frac{2n-1}{2N}\right)}^{2}\right)$$